The etiology and incidence of anaphylaxis in Rochester, Minnesota: A report from the Rochester Epidemiology Project - Decker, Wyatt W.; Campbell, Ronna L.; Manivannan, Veena; Luke, Anuradha; St. Sauver, Jennifer L.; Weaver, Amy; Bellolio, M. Fernanda; Bergstralh, Eric J.; Stead, Latha G.; Li, James T.C. (Journal of allergy and clinical immunology, 2008)
Reported incidences of anaphylaxis range from 3.2 to 20 per 100,000 population. The incidence and trend over time has meaningful public health implications but has not been well characterized because of a lack of a standard definition and deficiencies in reporting of events. We sought to determine the incidence and cause of anaphylaxis over a 10-year period. We performed a population-based incidence study that was conducted in Rochester, Minnesota, from 1990 through 2000. Anaphylaxis episodes were identified on the basis of symptoms and signs of mast cell and basophil mediator release plus mucocutaneous, gastrointestinal tract, respiratory tract, or cardiovascular system involvement. Two hundred eleven cases of anaphylaxis were identified (55.9% in female subjects). The mean age was 29.3 years (SD, 18.2 years; range, 0.8-78.2 years). The overall age- and sex-adjusted incidence rate was 49.8 (95% CI, 45.0-54.5) per 100,000 person-years. Age-specific rates were highest for ages 0 to 19 years (70 per 100,000 person-years). Ingested foods accounted for 33.2% (70 cases), insect stings accounted for 18.5% (39 cases), medication accounted for 13.7% (29 cases), radiologic contrast agent accounted for 0.5% (1 case), “other” causes accounted for 9% (19 cases), and “unknown” causes accounted for 25.1% (53 cases). The “other” group included cats, latex, cleaning agents, environmental allergens, and exercise. There was an increase in the annual incidence rate during the study period from 46.9 per 100,000 persons in 1990 to 58.9 per 100,000 persons in 2000 ( P = .03). The overall incidence rate is 49.8 per 100,000 person-years, which is higher than previously reported. The annual incidence rate is also increasing. Food and insect stings continue to be major inciting agents for anaphylaxis.